Using OS/2 Lotus SmartSuite - Weberg, Robert L. (Que, 1995)
The book is the ideal "one book" solution for finding essential information about the individual applications within the suite and maximizing their use together. This book covers all the applications in the suite so you can get started immediately with the individual products.